2020
DOI: 10.1038/s41467-020-15669-z
|View full text |Cite
|
Sign up to set email alerts
|

Origin of micro-scale heterogeneity in polymerisation of photo-activated resin composites

Abstract: Photo-activated resin composites are widely used in industry and medicine. Despite extensive chemical characterisation, the micro-scale pattern of resin matrix reactive group conversion between filler particles is not fully understood. Using an advanced synchrotron-based wide-field IR imaging system and state-of-the-art Mie scattering corrections, we observe how the presence of monodispersed silica filler particles in a methacrylate based resin reduces local conversion and chemical bond strain in the polymer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
2
15
0
2
Order By: Relevance
“…Their ratio in the composition is not disclosed [ 10 ]. Sirovica et al recently found the microscopic heterogeneity in the degree of conversion in the polymer network surrounding individually dispersed silica fillers [ 52 ]. Unsilanized silica fillers were encapsulated with polymer of a locally lower degree of conversion, causing internal strain and stresses [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their ratio in the composition is not disclosed [ 10 ]. Sirovica et al recently found the microscopic heterogeneity in the degree of conversion in the polymer network surrounding individually dispersed silica fillers [ 52 ]. Unsilanized silica fillers were encapsulated with polymer of a locally lower degree of conversion, causing internal strain and stresses [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sirovica et al recently found the microscopic heterogeneity in the degree of conversion in the polymer network surrounding individually dispersed silica fillers [ 52 ]. Unsilanized silica fillers were encapsulated with polymer of a locally lower degree of conversion, causing internal strain and stresses [ 52 ]. These events could facilitate water penetration in areas of a locally low degree of conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the significantly different influence of the two types of BG fillers on the DC of experimental composites enabled insight into shrinkage behaviour that was either governed by the changing DC (C-series) or that was DC-independent (E-series). As DC has been shown to be diminished at the boundary layer of resin that is immediately adjacent to filler particles, incorporating larger particles reduces total filler surface area and thus can be expected to improve DC 37 . This improvement in DC was not identified in our study when smaller reinforcing filler particles (d50 = 1 µm) were replaced by larger BG fillers (d50 = 3 µm).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inferior mechanical properties and transparencies were observed when 1.0 wt% or more MPC 1 was combined with PMMA, which we conclude to be due to significant differences in the physical properties of MPC and PMMA, such as density, molecular orientation, crystal structure, and crystallinity, which become more pronounced in composites with high MPC 1 concentrations. As a result, the addition of excess MPC resulted in a decrease in the strength of the PMMA composite, as structural heterogeneity with PMMA counteracts the increase in strength associated with the network structure of MPC [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%